Turnover Intention Among Nurses and Its Implications for Retention Strategies in Human Resource Management at Hospital X, Tangerang - Muhammad Iqbal; Sitti Rakhman (Paspama Institute, 2025)
Turnover intention among nurses has become a serious challenge for healthcare institutions. This phenomenon is influenced by various internal and external factors. It is essential for hospital management to understand the extent to which nurses intend to remain in their positions, as high turnover rates can negatively impact the quality of healthcare services and organizational stability. This study aims to identify the level of turnover intention among nurses at Hospital X in Tangerang using Mobley’s Turnover Intention Questionnaire, which consists of 10 Likert-scale items. The research adopts a descriptive quantitative approach with a univariate analysis. The population comprises 20 nurses who voluntarily participated in the study, and the sample includes the entire population. The findings reveal that 4 respondents (20%) have a low intention to leave their jobs, 13 respondents (65%) show a moderate level of turnover intention, and 3 respondents (15%) have a high intention to resign. These results suggest that HR management must take proactive measures to prevent these intentions from translating into actual resignations. Although a moderate level of turnover intention does not necessarily indicate a critical condition, it serves as an important signal of underlying dissatisfaction or discomfort in the work environment, which must be addressed through strategic interventions.